The Effect of Nursing Intervention-based Levine Conceptual Model Program on Rehabilitation Process among Fracture Patients - Henrianto Karolus Siregar; Dudut Tanjung; Nunung Febriany Sitepu (Jurnal Ners, 2020)
Introduction: The nursing intervention program is a strategy for the rehabilitation process among fracture patients The Levine conceptual model program is a practical nursing theory using energy conservation, energy, structural integrity, personal integrity, and social integrity. The study aims to identify the effect of nursing intervention based on Levine's theory of the rehabilitation process among fracture patients.Methods: A quasi-experimental with equivalent control group design was applied in this study. Sixty-two respondents were selected into the experimental group (n=31) and control group (n=31) by using a consecutive sampling technique. The patients' rehabilitation on fracture included sleep disorder, pain, anxiety, and family support as dependent variables. Researchers used the Sleep Quality Scale (SQS) instrument, the Numeric Rating Scale, the Hamilton Anxiety Rating Scale, and the family support scale. Data were analyzed using a Wilcoxon Signed Rank Test.Results: The results showed a significant effect of patients' recovery on fracture among patients after receiving Levine-based nursing intervention than before receiving the intervention (p <0.05). The results of research on the nursing intervention program are based on Levine's conceptual model of sleep disorders, pain, anxiety, and family support (p <0.05). In conclusion, there was significantly different nursing intervention based on Levine in   energy conservation, energy, structural integrity, personal integrity, and social integrity.Conclusion: The nursing intervention program based on Levine's conceptual model could be part of independent nursing intervention to deal with recovery in fracture patients. Based on this description, the researcher is interested in examining the effect of nursing intervention based on Levine’s conceptual model program on rehabilitation process among fracture patients.